Nutrition education and its relationship to body image and food intake in Asian young and adolescents: a systematic review - Pushpa, Baladandapla Shivappa; Abdul Latif, Siti Norhedayah; Sharbini, Sharimawati; Murang, Zaidah Rizidah; Ahmad, Siti Rohaiza (Frontiers in Nutrition, 2024)
Background: The literature brings to light the unhealthy nutritional habits prevalent among Asian adolescents and their high level of body image dissatisfaction. This study aims to conduct a systematic review of the literature on the effect of nutritional education interventions on their nutritional knowledge and food intake behavior, attitude, practice, and body image. Method: We searched relevant published studies in PubMed, Web of Science, Scopus, Science Direct, and Springer using the PICO framework. and performed a quality assessment using the ten-point checklist adapted from the National Institutes for Health tool. Results: The majority of the nutritional education interventions improve unhealthy food intake and body image misperception, particularly on nutritional knowledge/self-efficacy, healthy dietary habits, physical activities, and fruit and vegetable intake. We also found a negative association with excess weight gain, obesity, and unethical weight reduction practices, leading to dissatisfaction with body image. Conclusion: These interventions can help address dietary problems and body image perception and support the development of future interventions.